Validitas dan Kepraktisan E-Modul berbasis Kontekstual Mata Pelajaran OTK Sarana dan Prasarana untuk Peserta Didik Program Keahlian Otomatisasi Tata Kelola Perkantoran - Nurul Isnaini; Agung Listiadi; Waspodo Tjipto Subroto (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
This development research aims to develop contextual-based E-Module teaching materials for OTK sarana dan prasarana for class XI. In addition, this study aims to determine the feasibility of e-modules based on validation assessments and reviews by expert validators and to determine the level of practicality of e-modules developed based on teacher and student assessments after carrying out the trial phase. Thiagarajan's 4-D development model (Define-Design-Develop Disseminate) is used in the development of this e-module. This research was tested on 20 students of the OTKP expertise program class XI subjects OTK Sarana dan Prasarana. The data collection instrument used a material expert validation sheet, a linguist, a graphic expert, and a practicality questionnaire. Expert validation sheets and practicality questionnaires will be analyzed quantitatively using a Likert scale. Based on the results of the study, showed the feasibility of validating e-module teaching materials by expert validators categorized as very strong interpretation so that it was declared feasible to be used in learning activities, especially OTK Sarana dan Prasarana. Then based on the practicality assessment by teachers and students, the interpretation is categorized as very practical so that the e-module developed is stated to be very practical for use in OTK Sarana dan Prasarana.